Oral Storytelling, Speaking and Listening and the Hegemony of Literacy: Non-Instrumental Language Use and Transactional Talk in the Primary Classroom. Issue 1 (2nd January 2016) - Hibbin, Rebecca
Abstract: The oral re-telling of traditional tales, modelled by a storyteller and taught to children in school, can be understood as 'non-instrumental' practice in speaking and listening that emphasises oral language over the reading and writing of stories. While oral storytelling has significant benefits to children's education and development, it is under-utilised within Primary Education in the UK. This interview and library-based study explores participant perceptions of oral storytelling and the barriers to the utilisation of such non-instrumental practice in school. In addition, observation of an oral storytelling initiative provides a research context through which such perceptions are understood. The findings suggest that speaking and listening is implicitly devalued as a result of the elevation of instrumental literacy-based practice in the primary curriculum. In addition, enquiry into the specific effects of engaging with orality as a precursor to literacy development is lacking. It is suggested that while New Literacy Studies has enhanced our understanding of the interrelationship between the written and spoken word, it is less helpful when considering language as a 'continuum of spontaneity'. It is concluded that spoken language that is explicitly unattached to literacy-based outcomes should be strongly encouraged in school. In addition, it is important to understand on an empirical basis whether the attachment of a written outcome affects the way that spoken language practice is engaged with in the classroom.